Educational transformation in the digital era: Innovative strategies and character challenges in creating the 21st century generation - Imam Anas Hadi; Tri Widarti; Yatmi; Ian Fii Barril Hidayah; Miftachul Mahmud (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The transformation of education in the digital era has brought significant changes in the learning system, both in terms of methods, the role of teachers, and the competencies required of students. On the other hand, technological advances also present new challenges, especially related to the degradation of moral values and character. Therefore, it is important to examine how modern education can integrate technology, 21st-century learning strategies, and character education holistically. This study aims to analyze the transformation of digital education and innovative strategies in 21st-century learning, identify the challenges of character education in the digital era, and offer an integrative approach between technology and character formation in the education curriculum. The method used is qualitative descriptive through library research, by reviewing academic sources in the form of books, scientific journals, and national and international policy documents. The results of the study show that technology has the potential to increase the effectiveness of learning if accompanied by innovative strategies that focus on developing 4C competencies. However, character education remains a fundamental aspect that must be integrated into every learning process so that students not only excel academically, but also have integrity and social responsibility. Holistic integration between technology and character has proven to be a strategic solution to produce graduates who are adaptive, competitive, and have strong character in facing global challenges.